The Heist - Silva, Daniel, 1960-; Guidall, George (New York : Harper Audio, 2014)
"Legendary spy and art restorer Gabriel Allon is at work in Venice repairing an altarpiece when he receives an urgent summons from the Italian police. The art dealer Julian Isherwood has stumbled upon a murder scene in Lake Como, and is being held as a suspect. To save his friend, Gabriel must perform one simple task: find the most famous missing painting in the world"--
Keywords: Allon, Gabriel (Fictitious character) -- Fiction; Murder -- Fiction -- Investigation; Intelligence officers -- Fiction; Art restorers -- Fiction; Art thefts -- Fiction -- Investigation; Suspense fiction; Spy stories; Audiobooks